Feminism and Ethics: Narrow Ethical Theory as an Example - Faraj, Prof.Dr.Anwar Mohammed (Sulaimani Journal for Humanities, 2026)
This paper examines the relationship between feminism and ethics, with a particular emphasis on a feminist ethical theory known as “distress”. We will begin by introducing feminism from various perspectives, including encyclopedias, researchers, activists and international organizations. This introduction sets the stage for an in-depth discussion of salient issues related to gender inequality and injustice, thus providing an overview of the theory. A significant part of the paper focuses on the perspective of Alison Jagger, a prominent researcher whose contributions to feminist ethical theory are numerous and influential. In addition, we critically evaluate the theory by focusing on researchers and thinkers who have criticized it from different perspectives. This balanced approach enriches the ethical discourse and ensures an impartial assessment of the validity of the theory. Methodologically, the research proceeds from general to specific through a series of logical steps. We begin with a general introduction to feminism and gradually focus on feminist ethical theory. Our detailed exploration includes a section on Alison Jagger's views, allowing readers to gradually build their own understanding of the subject.
Keywords: Feminism; Ethics; Feminist Ethical Theory; Ethical Theory of Distress; Feminist Ethics; Alison Jagger